Uso de rotinas de aprendizado de máquina em prontuário eletrônico para apoio a diagnósticos de pacientes oftalmológicos - Alves, Lucas De Oliveira Batista [UNIFESP] (2021)
Objective: To implement artificial intelligence routines through machine learning to construct diagnostic prediction models with data from electronic medical records of patients from the Department of Ophthalmology of Hospital São Paulo. Method: Preparation of a literature review of the main techniques and solutions of machine learning to use in electronic medical records, 1. extraction, treatment and analysis of data from medical records of the Department; 2. construction and analysis of vectorization models of related words in the context of the Database of Hospital São Paulo; 3. construction and validation of diagnostic prediction models. Results: The word vectorization models were able to capture the semantics of medical terms and enabled the construction of diagnostic prediction models, making the prediction model a great tool to assist health professionals. Conclusion: The machine learning models showed potential results to assist as diagnostic support tools of ophthalmologic patients.